Eosinophilic pleural effusion in an eleven-year-old boy - Shakya, Kashyap Narsingh; Shrestha, Anup; Yadav, Arabindra; Gautam, Uttara; Panday, Rajesh Kumar; Lamichhane , Mira (Journal of Kathmandu Medical College, 2021)
Pleural effusion fluid with ?10% eosinophils may be seen in 5-16% of exudative pleural effusions. Its association with helminthic infestation is reported in the literature. This patient with left-sided eosinophilic pleural effusion was a referred case from another hospital and treated initially as parapneumonic. With inadequate response to antibiotics and a markedly high IgE level praziquantel was started. This resulted in rapid disappearance of symptoms, decrease in the eosinophil count, and radiological improvement. After exclusion of parapneumonic, tuberculosis, autoimmune disease, and malignancy, a trial of antihelminthics should be considered an option. This may spare unnecessary investigations.